The New Zealand Institute of Safety Management Health and Safety Reform Survey - Sissons, Jeff (New Zealand Journal of Health and Safety Practice, 2024)
This paper provides a high-level summary of the Health and Safety Reform Survey conducted by the New Zealand Institute of Safety Management (NZISM) in April 2024. The survey gathered insights from over 1,321 health and safety professionals in New Zealand on the effectiveness of the health and safety system (including key aspects of the Health and Safety at Work Act 2015 and its supporting regulations along with areas requiring improvement). Key findings indicate a general level of comfort with the existing Act, a desire for greater regulation of particular risks (psychosocial risks, plant and machinery, sector-specific) and a desire for a better-resourced and more focused WorkSafe with an emphasis on inspector capability and guidance development.